2019
DOI: 10.1021/acsbiomaterials.9b01395
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Single-Layered Graphene Quantum Dots Used for Diagnosis of Mitochondrial Malfunction-Related Diseases

Abstract: Mitochondria are critical organelles in eukaryotes that efficiently generate adenosine 5′-triphosphate (ATP) for various biological activities, and any defect in the process of ATP synthesis may lead to mitochondrial dysfunction and directly link to a variety of medical disorders. Monitoring the ATP variations in cells is key for innovative early diagnosis of mitochondrial diseases. Herein, multifunctional single-layered graphene quantum dots (s-GQDs) with bright green emission were constructed, which exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Abnormities in protein processing, Ca 2+ homeostasis and lipid metabolism may lead to ER stress and then activate the inflammatory pathway, both of which are closely related to the initiation and progression of atherosclerosis (Dong et al, 2016; Lale & Ira, 2016). We have reported that substitution of SERCA2 C674 thiol depletes ER Ca 2+ stores in ECs (Mei et al, 2014) and induces ER stress in ECs, SMCs, and renal proximal tubule cells (Jiang et al, 2020; Liu et al, 2020; Mei et al, 2014). In the present work, we found substitution of SERCA2 C674 in BMDMs upregulated the protein expression of ER stress markers (Figure 1b), including the ratio of phosphorylated PRKR‐like endoplasmic reticulum kinase protein kinase (p‐PERK) to total PERK (p‐PERK/PERK), activating transcription factor 6 (ATF6), binding immunoglobulin protein (BIP), and C/EBP homologous protein (CHOP), which could be reversed by 4‐phenyl butyric acid (PBA), an ER stress inhibitor (Figure 1b), confirming that the redox state of SERCA2 C674 is critical in controlling ER function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormities in protein processing, Ca 2+ homeostasis and lipid metabolism may lead to ER stress and then activate the inflammatory pathway, both of which are closely related to the initiation and progression of atherosclerosis (Dong et al, 2016; Lale & Ira, 2016). We have reported that substitution of SERCA2 C674 thiol depletes ER Ca 2+ stores in ECs (Mei et al, 2014) and induces ER stress in ECs, SMCs, and renal proximal tubule cells (Jiang et al, 2020; Liu et al, 2020; Mei et al, 2014). In the present work, we found substitution of SERCA2 C674 in BMDMs upregulated the protein expression of ER stress markers (Figure 1b), including the ratio of phosphorylated PRKR‐like endoplasmic reticulum kinase protein kinase (p‐PERK) to total PERK (p‐PERK/PERK), activating transcription factor 6 (ATF6), binding immunoglobulin protein (BIP), and C/EBP homologous protein (CHOP), which could be reversed by 4‐phenyl butyric acid (PBA), an ER stress inhibitor (Figure 1b), confirming that the redox state of SERCA2 C674 is critical in controlling ER function.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular calcium ion (Ca 2+ ) homeostasis is pivotal in maintaining the normal physiological processes of cells, and disrupted Ca 2+ regulation has been associated with metabolic disorders, diabetes, atherosclerosis and ageing (Jiang et al, 2020; Olgar et al, 2020; Zhu et al, 2019). The sarco/endoplasmic reticulum calcium ATPase (SERCA) is the only key player that actively transports cytoplasmic Ca 2+ into the sarcoplasmic or endoplasmic reticulum (ER) and exerts a pivotal role in maintaining the high Ca 2+ concentration of the ER (Wuytack et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic fluorescence of the GQDs was reduced dramatically when ssDNA was absorbed onto low-oxidized GQDs, suggesting that the GQD properties can be regulated by the polymer sequence and type. GQDs have also been shown to be effective in treating diseases, such as Alzheimer's disease [430], diabetes [431] and mitochondrial dysfunction [432]. For example, aggregation and transmission of α-synuclein (α-syn) in the midbrain may be related to the pathogenesis of Parkinson's disease.…”
Section: Therapy For Other Diseasesmentioning
confidence: 99%
“…This aspect is used as a probe for detecting mitochondrial dysfunction-related diseases. 59 Similarly, TPP-conjugated CdSe-ZnS quantum dots are used to target mitochondria in 8 h. 60 More recently, a <10 nm arginine-terminated quantum dot is designed that can efficiently target mitochondria within 1 h via the nonendocytic pathway. 44…”
Section: Mitochondriamentioning
confidence: 99%
“…Single layered graphene quantum dots can selectively bind with purine nucleotides of ATP present in mitochondria via π–π-stacking and electrostatic interaction. This aspect is used as a probe for detecting mitochondrial dysfunction-related diseases . Similarly, TPP-conjugated CdSe-ZnS quantum dots are used to target mitochondria in 8 h .…”
Section: Optical Nanomaterial-based Subcellular Targeting and Imagingmentioning
confidence: 99%